Assesing Child Abuse in Kisojo Archdeaconry, Mityana Diocese - Livingstone Nabaasa (Uganda Christian University, 2026)
The study aimed at assessing child abuse in Kisojo Archdeaconry, Mityana Diocese. It specifically focused on; identifying the forms of child abuse prevalent in Kisojo Archdeaconry, exploring how Christian parenting can be used to prevent the prevalence of child abuse in Kisojo Archdeaconry, and examining what the strategies the Church can adopt to end child abuse in Kisojo Archdeaconry, Mityana Diocese. This study was conducted using an explanatory sequential design where a mixed method research approach (both quantitative and qualitative) was used. During the data gathering process, both purposive and simple random sample techniques were applied, along with questionnaires and interviews. A sample size of 100 respondents who are registered Christians of Kisojo Archdeaconry and 10 key informants who are clergy, police and local leaders from Kisojo Archdeaconry, Mityana Diocese were used in the study. The findings revealed that child abuse in Kisojo Archdeaconry is a significant concern, with physical punishment, emotional abuse, child labor, neglect, sexual and verbal abuse being widely acknowledged. Although Christian parenting is recognized as a vital tool in preventing abuse promoting love, patience, and discipline; it is challenged by cultural practices, ignorance of biblical principles, and poverty. The Church is viewed as a central and trusted institution capable of combating child abuse through regular sensitization, enhanced counseling services, Christian parenting teachings, and active collaboration with local authorities and civic leaders to promote child protection. Lastly, the study recommended that the Church in Kisojo Archdeaconry actively combat child abuse through regular community sensitization, provision of counseling and pastoral care, collaboration with local authorities for effective case handling, integration of Christian parenting education into discipleship programs, and prophetic advocacy against harmful cultural norms that justify abuse. These faith-based interventions are seen as vital for transforming parenting practices and promoting child protection within the community.
Undergraduate research